Locating Sembène’s mégotage in Zimbabwe’s kiya kiya video-film production - Ureke, Oswelled (Routledge, 2021)
The main objective of this paper is to develop a macro-level account of the film industry in contemporary Zimbabwe by exploring the role of its people, infrastructure and institutions in past and current film production efforts. The article is informed by Ousmane Sembène’s view of filmmaking in Africa as mégotage (cigarette-butt cinema). Sembène’s memorable description is used as a way to think about the production efforts and infrastructure constituting the Zimbabwean film industry, characterised as a constellation of numerous informal, entrepreneurial endeavours. Interviews were carried out with carefully selected Zimbabwean filmmakers and policy-makers to gain their insights on industry prospects and challenges, and a thematic analysis was employed to analyse the context-rich data. The paper shows that, contrary to popular sentiments that there is no film industry in Zimbabwe, there are many encouraging endeavours in the country, that are thriving with little or no support. Such efforts include self-funding for films, as well as filmmakers exhibiting their own work to raise funds for future production. NGOs have also continued offering support, though peripherally and not always with positive results.